2005
DOI: 10.1130/1052-5173(2005)015<4:ulpamg>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Urban Lead Poisoning and Medical Geology: An Unfinished Story

Abstract: The intersection between geological sciences and human health, termed medical geology, is gaining significant interest as we understand more completely coupled biogeochemical systems. An example of a medical geology problem largely considered solved is that of lead (Pb) poisoning. With aggressive removal of the major sources of Pb to the environment, including Pb-based paint, leaded gasoline, and lead pipes and solder, the number of children in the United States affected by Pb poisoning has been reduced by 80%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 115 publications
(71 citation statements)
references
References 31 publications
5
65
0
Order By: Relevance
“…In contrast, there is a body of literature suggesting that Pb accumulates in soils from multiple sources, and particularly from two main sources, paint and gasoline, determine the footprint, and hence childhood Pb exposure (Reagan and Silbergeld 1989;Filippelli et al 2005;Laidlaw et al 2005;Mielke and Reagan 1998;Johnson and Bretsch 2002). This divergent opinion is critical because it has implications regarding steps needed to protect children in urban areas from exposure to Pb.…”
Section: Introductionmentioning
confidence: 89%
“…In contrast, there is a body of literature suggesting that Pb accumulates in soils from multiple sources, and particularly from two main sources, paint and gasoline, determine the footprint, and hence childhood Pb exposure (Reagan and Silbergeld 1989;Filippelli et al 2005;Laidlaw et al 2005;Mielke and Reagan 1998;Johnson and Bretsch 2002). This divergent opinion is critical because it has implications regarding steps needed to protect children in urban areas from exposure to Pb.…”
Section: Introductionmentioning
confidence: 89%
“…If the particulate Pb was deposited instead on a grassy fringe, like a front yard or park, the Pb was effectively retained. In such a setting, the insolubility of Pb leads to its concentration in the surface layer of soils, which can reach levels above 1000 parts per million (ppm) in cities (e.g., Filippelli et al, 2005). Thus, surface soils became the repositories of Pb deposited over decades-in the case of older roadways, the proximal soils retained almost all of the Pb deposited on them over a period of about 60 years.…”
Section: Roadway Sources Of Pbmentioning
confidence: 99%
“…One of the characteristics of Pb distribution in surface soils of several older cities is a distinct decreasing trend from city center to suburban surroundings, a legacy both of Pb deposition, redistribution and smearing of original point sources, and less Pb deposition in newer suburban neighborhoods due to recent Pb controls (e.g., Mielke et al, 1984;Filippelli et al, 2005;Johnson and Bretsch, 2002;Roux and Marra, 2007). The urban roadway example shows both the impact of the point source of Pb deposition from leaded gasoline as well as the diffuse soil Pb that blankets urban regions.…”
Section: Diffuse Soil Pb and Children's Healthmentioning
confidence: 99%
“…This type of distribution has been observed for Pb in other urban studies (e.g. Birke and Rauch, 2000;Filippelli et al, 2005) and is generally attributed to traffic-related Pb emissions, prior to the ban on leaded petrol. Root (2000) suggested that Pb wheel-balancing weights, which are dropped from vehicle wheels and pulverized by traffic, may represent an important source of Pb near urban roadways.…”
Section: Spatial Distribution Of Element Concentrations Related To Anmentioning
confidence: 66%
“…Chen et al, 1997;Wilcke et al, 1998;Li et al, 2001;M€ uller et al, 2001;Lu et al, 2003;Wang et al, 2005;Duzgoren-Aydin et al, 2006). Urban soil geochemical mapping studies, including those performed by sampling along a limited number of transects across an urban area, conducted in the USA include the cities of Pueblo, Colorado (Diawara et al, 2006), New Orleans, Louisiana (Mielke, 1994;Mielke et al, 2000Mielke et al, , 2001, Cincinnati, Ohio (Turer et al, 2001), Gainesville and Miami, Florida (Chirenje et al, 2003), Chicago, Illinois (Khan et al, 1973;Shinn et al, 2000;Cannon and Horton, 2009), Indianapolis, Indiana (Filippelli et al, 2005), Syracuse, New York (Griffith et al, 2009), New York City (Pouyat and McDonnell, 1991) and Lubbock, Texas (Brown et al, 2008). This account presents results from a 2005 geochemical mapping study of soils in the Denver, Colorado (USA), metropolitan area, and compares the resulting data set with new data generated from samples collected during an unpublished study conducted in 1972.…”
Section: Introductionmentioning
confidence: 99%